Functional Contracting: Re-Conceptualizing Business Contracts in the Face of New Forms of Production - Viljanen, Mika; Salminen, Jaakko; Hurmerinta-Haanpää, Anna (University of Georgia, School of law, 2025)
Alongside bilateral one-off transactions, contracts are used to govern the dynamic, multi-tiered production networks that constitute a majority of global commerce today. Contract law and contract theory do not reflect this change in contractual modalities. In this paper, we look first to summarize earlier theories of contract and posit that the theory of functional contracting offers a novel and more useful approach for understanding contractually governed dynamic and multitiered transactions. We then underscore the difference between functional contracting and earlier theories by describing a recent practical case on the contractual governance of business-model transitions. Finally, on the basis of the theoretical comparison, case study, and other related case studies, we evaluate how the model of functional contracting helps legal scholars and practitioners to understand changes in contractual modalities brought about by recent changes in the global economy.